2004
DOI: 10.1002/chin.200418232
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of Prenylated and Benzylated Pterocarpans Against Snake Venom.

Abstract: Synthesis and Pharmacological Evaluation of Prenylated and Benzylated Pterocarpans Against Snake Venom. -Analogues of the natural pterocarpan edunol (IXf) are designed and synthesized. The antimyotoxic, antiproteolytic and PLA2 inhibitor activity of the natural product are improved by replacement of the prenyl group at position 4 by a benzyl group [cf. (IXa)]. -(DA SILVA, A. J. M.; COELHO, A. L.; SIMAS, A. B. C.; MORAES, R. A. M.; PINHEIRO, D. A.; FERNANDES, F. F. A.; ARRUDA, E. Z.; COSTA*, P. R. R.; MELO, P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…These represent the second largest identified group of isoflavonoids, after the isoflavones, and are produced by leguminous plants as phytoalexins, defense substances synthesized against pathogen attack [1]. Many pterocarpans have shown potent biological activities against viruses, microbes, snakebites and different animal cellular systems [2], [3]. According to several authors, flavonoids and isoflavonoids are especially promising candidates for cancer prevention [4].…”
mentioning
confidence: 99%
“…These represent the second largest identified group of isoflavonoids, after the isoflavones, and are produced by leguminous plants as phytoalexins, defense substances synthesized against pathogen attack [1]. Many pterocarpans have shown potent biological activities against viruses, microbes, snakebites and different animal cellular systems [2], [3]. According to several authors, flavonoids and isoflavonoids are especially promising candidates for cancer prevention [4].…”
mentioning
confidence: 99%
“…Several other plants with antiphopholipase A 2 and antivenom properties were described: (i) the root extract from Mimosa pudica neutralized myotoxins, toxic enzymes and lethality from Naja kaouthia venom; (ii) methanolic extracts of roots from Hemidesmus indicus and H. pluchea inhibited the hemorrhagic and lethal effects of Vipera ruselli venom; (iii) the methanolic extract from Eryngium creticum inhibited the hemolytic activity of Leiurus quinquestriatus http://www.ncbi.nlm.nih.gov/entrez/query.fcgi?cmd=Search&d b=pubmed&term=leiurus+quinquestriatus&tool=fuzzy&ot=Lei urus+quinquesteiartus> scorpion venom; (iv) decrease of the lethal effect of C. d. terrificus venom by the extract from Peschiera fuchsiaefolia was also reported; (v) the venoms from Naja nigricollis and Echis ocellatus had their neurotoxic and myotoxic activities inhibited by the methanolic extract from Parkia biglobosa bark; (vi) the methanolic extract from other Indian plants (Vitex negundo and Emblica officinalis) neutralized the hemorr-hagic, coagulant and inflammatory effects of Vipera russellii and Naja kaouthia venoms; (vii) preliminary studies showed the inhibitory activity of the extract from Marsypianthes chamaedrys against the clotting activity of B. jararaca venom; (ix) Musa paradisiaca, an important food all over the world, also showed antiophidian properties against PLA 2 , myotoxic, hemorrhagic and lethal activities of Crotalidae venoms; (x) inhibitory effects of the compound arturmerone isolated from Curcuma longa, able to neutralize the hemorrhagic activity of B. jararaca venom and the lethal effect of C. d. terrificus venom was also showed [88,[103][104][105][106][107][108][109][110][111] da Silva et al [99] isolated edunol, a pterocarpan from Harpalyce brasiliana, with antimyotoxic and antiproteolytic activities against B. jararacussu venom, besides expressive PLA 2 s inhibitory properties. Recently, rosmarinic acid, isolated from Cordia verbenacea, known as "erva baleeira" (Waler herb), was shown to neutralize the PLA 2 s BthTX-I and II from B. jararacussu snake venom [6,112] (Fig.…”
Section: Plant Extracts and Their Isolated Pla 2 S Inhibitorsmentioning
confidence: 97%
“…Chandra et al [117] showed, by crystallography, the aristolochic acid-alkaloid-Vipera russelli PLA 2 s complex. Some natural pterocarpans have been isolated from plants, showing inhibitory activity against venom PLA 2 s. da Silva et al [99] produced synthetic pterocarpans able to inhibit the myotoxic and PLA 2 activities of B. jararacussu.…”
Section: Plant Extracts and Their Isolated Pla 2 S Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the highest incidence of ophidic accidents is related to different genres of the family Viperidae snakes (Silva et al, 2004). Effective treatment is administration of antivenom, which is determined according to the genre of the snake (Lallo and Theakston, 2003).…”
Section: Introductionmentioning
confidence: 99%